REDUCING THE CARBON FOOTPRINT BY MAKING GEOPOLYMER MATERIALS FOR CEMENT-FREE CONSTRUCTION BASED ON WASTE AND INDUSTRIAL BY-PRODUCTS (Nonconventional Technologies Review, 2024)
High-strength cement-free geopolymer concrete with 62.9 MPa (after 28 curing days) was experimentally produced from blast furnace slag, recycled concrete, and metakaolin as alumina-silicate binders as well as silica fume as silica-rich ultra-fine powder. Combining slag with metakaolin and silica fume allowed to increase its proportion up to 58.1 wt. %, without affecting shrinkage and hardness. Residual concrete from demolition was also used for making the geopolymer concrete as coarse aggregate as well as alumina-silicate binder together with fly ash, but not with granulated slag, metakaolin, and silica fume, this constituting the paper originality.
Keywords: geopolymer concrete; alumina-silicate binder; granulated slag; recycled concrete; metakaolin